The Effectiveness of Canva-Based Learning in Improving Students’ Visual Literacy - Fitria, Nur Annisa; Hamid, Abdulloh; Novitasari, Dian Candra Rini; Indriyani, Jiphie Gilia (UMSU, 2025)
This study aims to measure the effectiveness of Canva-based learning in improving visual literacy among students, given the importance of the ability to interpret, understand, and communicate meaning through visual elements in the digital age. This study used a pre-experimental method with a One Group Pre-test Post-test design, which was conducted at SDN Bejijong 2 Trowulan Mojokerto in May with 32 fifth-grade students as research subjects. Data were collected through pre-tests and post-tests using the Canva application to measure the improvement in students' visual literacy, with 11 indicators according to Avgerinou. Data analysis was performed using SPSS, with the results of the Paired Sample T -Test showed a significant increase in the post-test average score (49.16) compared to the pre-test (37.13), with a difference of 12.03 points and a significance value of 0.000 (p 0.05), which clearly proves that Canva is effective in improving students' visual literacy.